Infant feeding practices and risk of occurrence of diarrheal and respiratory infections in infancy-a hospital based study - Sharma, Rakesh; Sood, Arvind; Nair, Priyanka (International Journal of Contemporary Pediatrics, 2017)
Background: Breastfeeding is the most cost-effective intervention for protecting children against various childhood morbidities. Suboptimal breastfeeding has been linked with numerous adverse child health outcomes including increased incidence of diarrheal disease and pneumonia. Methods: A sample of 360 infants was surveyed during the period of one year (2013-2014). The socio-demographic characteristics and feeding modes were collected from the parents of the children during the interview. Results: A total of 228 (63.3%) were suffering from acute gastroenteritis and 132 (37.7%) were suffering from pneumonia. The risk of diarrhea and pneumonia was higher and statistically significant in partially breastfed and non- exclusive breast fed as compared to exclusive breast fed. Infants who were bottle fed had higher risk of morbidity. Infants who were breast fed for longer duration (more than 4 months) has lesser risk of morbidity as compare to counterparts who were fed for lesser duration. Conclusions: These results indicate that promoting exclusive breastfeeding will play an important role in reducing the risk of infantile diarrhoea and pneumonia. This observation is important given the growing concern of the modern society wherein breastfeeding is on the decline.